Building scalable web apps with Python and Google Cloud platform - Sanderson, Dan (O'Reilly, 2015)
"We all know Python is well suited to building web applications. It also happens to be a great choice for building on Google Cloud Platform, Google's suite of cloud hosting services. In this presentation, Google engineer and O'Reilly author Dan Sanderson shows how to set up a Python cloud development environment, build a scalable web app using various Google services and tools, and deploy and manage a live application."--Resource description page.